Recent Advances in Placenta–Heart Interactions - Maslen, Cheryl L. (Frontiers in Physiology, 2018)
Congenital heart defects (CHD) occur in ~1 in every 100 live births. In addition, an estimated 10% of fetal loss is due to severe forms of CHD. This makes heart defects the most frequently occurring birth defect and single cause of in utero fatality in humans. There is considerable evidence that CHD is heritable, indicating a strong contribution from genetic risk factors. There are also known external environmental exposures that are significantly associated with risk for CHD. Hence, the majority of CHD cases have long been considered to be multifactorial, or generally caused by the confluence of several risk factors potentially from genetic, epigenetic and environmental sources. Consequently, a specific cause can be very difficult to ascertain, although patterns of associations are very important to prevention. While highly protective of the fetus, the in utero environment is not immune to insult. As the conduit between the mother and fetus, the placenta plays an essential role in maintaining fetal health. Since it is not a fully-formed organ at the onset of pregnancy, the development of the placenta must keep pace with the growth of the fetus in order to fulfill its critical role during pregnancy. In fact, the placenta and the fetal heart actually develop in parallel, a phenomenon known as the placenta-heart axis. This leaves the developing heart particularly vulnerable to early placental insufficiency. Both organs share several developmental pathways, so they also share a common vulnerability to genetic defects. In this article we explore the coordinated development of the placenta and fetal heart and the implications for placental involvement in the etiology and pathogenesis of CHD.